Restorative Environmental Law Enforcement: Ensuring Environmental Restoration and Compliance Through Multiple Legal Instruments - Ndaru, Felix Aglen (Association of Certified Fraud Examiners Indonesia Chapter, 2025)
Indonesia faces massive pressure from environmental crimes. The environmental sector has fraud risk from money laundering and corruption. Traditional practices of law enforcement are not enough to create compliance. Innovative instruments are required; one of them is environmental restorative justice. The restorative justice approach in Indonesia has been formalized by several agencies since 2012, but there are no specific regulations on restorative justice in the environmental sector. This study intends to seek the conception of law enforcement built upon environmental restorative justice and how to implement environmental restorative justice in Indonesia. The study applies normative legal research methods by analyzing descriptively the legal instruments in Law Number 32 of 2009. The study shows that environmental law enforcement using environmental restorative justice is not a case termination, but rather a process of restoring the environment as the victim of environmental crime and broadening the liability of the main perpetrators. Restorative environmental justice in Indonesia can be implemented through the application of multiple legal instruments in the form of administrative sanctions, environmental dispute resolution, and criminal enforcement.